Evaluation of Liver Function Tests in Normal Pregnancy-An Observational Epidemiological Study-Kumbakonam Urban Rural Epidemiological Study-KURES 10: Life Sciences-Health - M, Suchitra; T S, Shanthi; S, Parthasarathy (International Journal of Life Science and Pharma Research, 2022)
Early interpretation of liver function tests (LFTs) can result in timely management and it may decrease the incidence of complications in both the mother and the foetus. Normal LFTs don't always imply a normal liver. A number of drawbacks can occur when interpreting basic blood LFTs. Abnormal Liver Function Tests (LFTs) in pregnancy must be properly interpreted to avoid diagnostic pitfalls. we did a routine testing in 498 asymptomatic antenatal mothers in the third trimester. Ninety-seven percentage of mothers had normal bilirubin while 93 % had normal enzyme levels. The other abnormal values were also within 1 to 1.5 % above the normal. No mother had any symptoms. Only two patients had gallstones whose LFTs were normal. Two mothers had tattoo marks while the other two were HbSAg positive. All the 498 mothers had an uneventful progress towards delivery. Cross consultation done on a few cases with abnormal values were non-contributory. Pregnancy-related disorders are the most common reason for unusual liver function tests during pregnancy, especially in the third trimester. We omitted such cases to support our hypotheses of avoiding undue testing. The most prevalent is pre-eclampsia-related disorder. This is the first such study on a huge sample size. We suggest a routine testing of LFTs is not needed in otherwise healthy antenatal mothers.